VISIBILITY OF THE BANYUMAS DIALECT IN THE ACADEMIC ENVIRONMENT AS A MINORITIZED LANGUAGE: A LINGUISTIC LANDSCAPE STUDY - Yulian Purnama; Linda Ayu Darmurtika; I Made Sutama; Putu Dewi Merlyna Yuda Pramesti; Kadek Wirahyuni (PT. LITERASI SAINS NUSANTARA, 2026)
Research on minority languages in linguistic landscapes has predominantly focused on languages that are taxonomically distinct from the state language. However, Gorter, Cenoz, and Marten criticize this narrow approach and propose that the concept of